Bone Marrow Stromal Cell Antigen 2: Is a Potential Neuroinflammation Biomarker of SOD1G93A Mouse Model of Amyotrophic Lateral Sclerosis in Pre-symptomatic Stage - Xu, Xiaojiao; Zhang, Jingjing; Li, Song; Al-Nusaif, Murad; Zhou, Qinming; Chen, Sheng; Le, Weidong (Frontiers in Neuroscience, 2022)
Neuroinflammation has long been thought to be associated with amyotrophic lateral sclerosis (ALS) development and progression. However, the exact molecular mechanisms of neuroinflammation underlying ALS remain largely unknown. In the present study, we attempted to elucidate the genetic basis of neuroinflammation in ALS by comparing the transcriptomic profile of the anterior horns of the lumbar spinal cord (AHLSC) between SOD1G93A mice and their wild-type littermates. Our results revealed that immune-related genes were selectively up-regulated in the AHLSC of presymptomatic ALS mice (40 days of age) compared to age-matched wild-type control mice. Notably, the differential expression level of these immune-related genes became more significant at the symptomatic stage of disease (90 days of age) in the ALS mice. Subsequently, eight genes involved in innate immune response in the AHLSC of ALS mice were further validated by qRT-PCR analysis. Of these genes, bone marrow stromal antigen 2 (BST2) was found for the first time to be significantly higher in the AHLSC of presymptomatic ALS mice when compared with wild-type mice. The increasing trend of BST2 expression became more obvious in the symptomatic stage. Immunofluorescent staining further confirmed that BST2 is mainly expressed on microglia in the AHLSC of ALS mice. These findings support the view that immune-related neuroinflammation is involved in the early pathogenesis of ALS, and BST2 may serve as a potential target for ameliorating microglia-mediated neuroinflammation pathologies in ALS.